Exploring the Use of Iris Species: Antioxidant Properties, Phytochemistry, Medicinal and Industrial Applications - Sohaib Khatib; Cecilia Faraloni; Latifa Bouissane (MDPI AG, 2022)
The genus Iris from the Iridaceae family consists of more than 262 recognized species. It is an ornamental and medicinal plant widely distributed in the Northern Hemisphere. Iris species convey a long history as valuable traditional drugs with a wide variety of applications in various cultures, having been recorded since medieval times. Currently, Iris spp. still find application in numerous fields, including cosmetics, pharmaceutics and the food industry. Moreover, many of their empirical uses have been validated by in vitro and in vivo studies, showing that Iris spp. exhibit potent antioxidant, anticancer, anti-inflammatory, hepatoprotective, neuroprotective and anti-microbial properties. Phytochemicals investigations have revealed that the plant extracts are rich in phenolic compounds, especially flavonoids and phenolic acids. As such, they constitute a promising lead for seeking new drugs with high susceptibilities towards various health issues, particularly oxidative-stress-related diseases such as cancers, neurodegenerative diseases, cardiovascular diseases, diabetes, etc. Herein, we present a literature review of the genus Iris intending to determine the plant's chemical profile and establish a coherent overview of the biological applications of the plant extracts with reference to their traditional uses.